Some studies on the geometry of block triangular matrices - Leong, C.W. (2011)
In this talk, we will present some latest studies of surjective mappings preserving bounded distance in both directions on matrix spaces, which is an continuation study of adjacency preserving mappings. Some recent works on surjective mappings preserving bounded distance in both directions on block triangular matrix algebras will be discussed.